Кон Simon LeVay, Queer Science: The Use and Abuse of Research into Homosexuality: Për Simon LeVay, Queer Science: The Use and Abuse of Research into Homosexuality - Badarevski, Bobi; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Bobi Badarevski | Боби Бадаревски Title (Macedonian): Кон Simon LeVay, Queer Science: The Use and Abuse of Research into Homosexuality Title (Albanian): Për Simon LeVay, Queer Science: The Use and Abuse of Research into Homosexuality Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 179-180 Page Count: 2 Citation (Macedonian): Боби Бадаревски, „Кон Simon LeVay, Queer Science: The Use and Abuse of Research into Homosexuality“, Идентитети: списание за политика, род и култура, т. 1, бр. 2 (зима 2001): 179-180. Citation (Albanian): Bobi Badarevski, „Për Simon LeVay, Queer Science: The Use and Abuse of Research into Homosexuality“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002): 179-180.